Immature platelet fraction in children infected with dengue fever - S., Amrutha B.; E., Adarsh; Y., SreeKrishna; Naidu, Apoorva; N., Shivtej (International Journal of Contemporary Pediatrics, 2018)
Background: Millions are infected with dengue every year. Early diagnosis of dengue infection is important for proper treatment of DHF and DSS to avoid fatal outcome. Thrombocytopenia is a common hematological abnormality in dengue, which demands platelet transfusion in most of the severe dengue cases. Platelet transfusion though life-saving has its own hazards. Hence, we can use some new parameter like immature platelet fraction (IPF) which is a measure of reticulated platelets that reflects the rate of thrombopoiesis. The risk of platelet transfusion may be decreased by rapid identification of immature platelet fraction. This study was performed to establish reference of IPF values for the assessment of thrombopoiesis. Methods: Blood samples from 150 children were obtained on day of illness 3, 5 and 7. The IPF is identified by sysmex XE2100 hematology analyser in the reticulocyte channel using a fluorescent dye and a carefully designed gating system and counted by a special software termed IPF master7. IPF values against platelet count were assessed separately on day 3, 5 and 7. Results: The reference intervals of IPF > 8 % and IPF < 8 % were assessed against platelet count. Increase in IPF favored increase in platelet count on day 5 which was statistically significant with the p value <0.001. Conclusions: A rapid and inexpensive automated measurement of IPF can be integrated as a standard parameter to evaluate the thrombopoietic state of the bone marrow. From the study it can be concluded that IPF is an important predictor of increase in platelet count. Increase in IPF>8 % suggests that platelet count will be increased in next 24 to 48hrs indicating that further blood transfusion will not be required.